Utility of a laboratory score in the prediction of altered autonomic nervous system function in autoimmune gastritis - Kalkan, Çağdaş; Soykan, İrfan (Turkish Journal of Gastroenterology, 2018)
Abstract Background/Aims: Autoimmune gastritis patients may have autonomic nerve dysfunction. The goal of our study was to explore the predictive value of two scoring systems in the differentiation of altered autonomic nerve function in autoimmune gastritis patients. Materials and Methods: Seventy-five patients with autoimmune gastritis were evaluated by using cardiovascular reflex tests in order to delineate autonomic nerve function. Data were analyzed by using two laboratory-based scoring systems: “global score” (hemoglobin, mean corpuscular volume, gastrin, vitamin B12, and chromogranin A) and “simple score” (hemoglobin, mean corpuscular volume, gastrin) in order to discriminate deranged and normal autonomic nerve function. Results: Mean “simple” and “global” scores were significantly higher in subjects with altered autonomic dysfunction than in subjects with normal autonomic function (3.55±1.88 vs. 0.908±0.409, p Conclusion: Simple score and global score have a high predictive value in the assessment of autoimmune gastritis patients with autonomic nerve dysfunction. These scoring systems may help physicians while evaluating autoimmune gastritis patients for the existence of autonomic nerve dysfunction instead of complex cardiovascular reflex tests. Cite this article as: Kalkan Ç, Soykan İ. Utility of a laboratory score in the prediction of altered autonomic nervous system function in autoimmune gastritis. Turk J Gastroenterol 2018; 29: 31-4.